Bioaugmentation of a rotating biological contactor for degradation of 2-fluorophenol - Duque, Anouk F. (2012)
The performance of a laboratory scale rotating biological contactor (RBC) towards shock loadings of 2-fluorophenol (2-FP) was investigated. During a period of ca. 2 months organic shock loadings of 25 mg L-1 of 2-FP were applied to the RBC. As no biodegradation of 2-FP was observed, bioaugmentation of the RBC with a 2-FP degrading strain was carried out and, along ca. 6 months, organic shock loadings within a range of 25-200 mg L-1 of 2-FP were applied. Complete biodegradation of 50 mg L-1 of 2-FP was observed during operation of the reactor. The RBC showed to be robust towards starvation periods, as after ca. 1 month of non-supply of the target compound, the reactor resumed 2-FP degradation. The inoculated strain was retained within the biofilm in the disks, as the 2-FP degrading strain was recovered from the biofilm by the end of the experiment, thus bioaugmentation was successfully achieved.